2021
DOI: 10.3390/antibiotics10040385
|View full text |Cite
|
Sign up to set email alerts
|

Finding What Is Inaccessible: Antimicrobial Resistance Language Use among the One Health Domains

Abstract: The success of a One Health approach to combating antimicrobial resistance (AMR) requires effective data sharing across the three One Health domains (human, animal, and environment). To investigate if there are differences in language use across the One Health domains, we examined the peer-reviewed literature using a combination of text data mining and natural language processing techniques on 20,000 open-access articles related to AMR and One Health. Evaluating AMR key term frequency from the European PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The results of this study can be considered to show that there is room for improvement in following the Findable, Accessible, Interoperable and Reusable (FAIR) principle for the reuse of scientific data ( 31 , 32 ). Similar conclusions were recently reached also by Wind et al ( 33 ) who recommended to utilize the term “One Health” in the title and abstract of publications about antimicrobial resistance that pertain to the One Health domain. Our observations support that recommendation, and widening it to the whole One Health domain.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study can be considered to show that there is room for improvement in following the Findable, Accessible, Interoperable and Reusable (FAIR) principle for the reuse of scientific data ( 31 , 32 ). Similar conclusions were recently reached also by Wind et al ( 33 ) who recommended to utilize the term “One Health” in the title and abstract of publications about antimicrobial resistance that pertain to the One Health domain. Our observations support that recommendation, and widening it to the whole One Health domain.…”
Section: Discussionsupporting
confidence: 82%
“…pygetpapers getpapers was written in NodeJS and has now been completely rewritten in Python3 (pygetpapers) for easier distribution and integration. Typical use of getpapers is shown in a recent paper (Wind et al, 2021) where the authors "analyzed key term frequency within 20,000 representatives [Antimicrobial Resistance] articles".…”
Section: Statement Of Needmentioning
confidence: 99%
“…Framing the right narrative for ABR at the ground level to engage local communities and creating a bottom-up process to supplement national and sub-national action plans have been challenging [9]. Studies have shown that there are also language and perceptional issues associated with ABR [10].…”
Section: Introductionmentioning
confidence: 99%